MECHATRONICS TECHNOLOGICAL SYSTEMS INTELLECTUAL MANAGEMENT PROSPECTS AND RESULTS - Andrey K. Tugengold; Valery P. Dimitrov; Lyudmila V. Borisova; Evgeny A. Lukyanov; Vladimir A. Gerasimov (Advanced Engineering Research)
DSTU outlook on research in mechatronics management intellectual systems creation is considered. Agricultural harvesting machine control problems are considered as examples.